Angiogenesis and experimental hepatic fibrosis - Queli Teixeira Lemos; Zilton A Andrade (Memorias do Instituto Oswaldo Cruz, 2010)
Angiogenesis is a basic change occurring during repair by granulation tissue. This process seems to precede fibrosis formation in most types of chronic liver disease. To examine its presence and significance in different types of hepatic insults, this paper sought to identify the presence, evolution and peculiarities of angiogenesis in the most common experimental models of hepatic fibrosis. The characterization of cells, vessels and extracellular matrix and the identification of factors associated with endothelium (factor VIII RA), vascular basement membrane, other components of the vascular walls (actin, elastin) and the presence of the vascular-endothelial growth factor were investigated. The models examined included Capillaria hepatica septal fibrosis, whole pig serum injections, carbon tetrachloride administration, main bile duct ligation and Schistosoma mansoni infection. The first four models were performed in rats, while the last used mice. All models studied exhibited prominent angiogenesis. The most evident relationship between angiogenesis and fibrosis occurred with the C. hepatica model due to circumstances to be discussed. Special attention was paid to the presence of pericytes and to their tendency to become detached from the vascular wall and be transformed into myofibroblasts, which is a sequence of events that explains the decisive role angiogenesis plays in fibrosis.